The Effect of Project Based Learning Model with STEAM Approach on Creative Thinking Skills of Grade VIII Students of SMP Negeri 27 Padang - Suci Indah Sari; Rani Oktavia; Febri Yanto (Pendidikan IPA, FMIPA, UNP, 2026)
This research is motivated by the importance of creative thinking skills in today's learning environment. This can be enhanced through the application of innovative learning models. One such approach is the Project-Based Learning model with a STEAM approach. This study aims to determine the effect of the Project-Based Learning model with a STEAM approach on the creative thinking skills of eighth-grade students at SMP Negeri 27 Padang. This study employed a quantitative method using a Quasi-Experimental method with a Non-Equivalent Control Group Design. The Project-Based Learning (PjBL) model with a STEAM approach was applied to the experimental class, while the conventional learning model was applied to the control class. Two classes served as sample groups, selected by purposive sampling. The research instruments used were observation sheets on the implementation of the Project-Based Learning (PjBL) model with a STEAM approach, descriptive test questions, and a questionnaire assessing student responses to the Project-Based Learning (PjBL) model with a STEAM approach. Data analysis was performed using normality tests, homogeneity tests, and two-mean difference tests. Statistical analysis in this study was performed using Microsoft Excel. The results of the study were obtained, based on the hypothesis test, the t-value was 5.70 ≥ t-table of 2.00. This indicates that there is a significant average difference, so that the Project Based Learning learning model with the STEAM approach has a significant effect on the creative thinking skills of class VIII students at SMP Negeri 27 Padang.